Therapeutic potential of selenium nanoparticles - K, Deepasree; Venugopal, Subhashree (Frontiers in Nanotechnology, 2022)
Diseases have always been a disconcerting issue and have changed into being an inevitable member of the world’s population. Medical advancements have brought in improved treatments for particular ailments, but unfortunately those betterments have resulted in either side effects or turned out futile to a certain extent. The emergence of nanotechnology has considerably benefitted medical experts in disease diagnosis and therapeutics. Currently, an expansive range of nanoparticles is being explored for their effectiveness in therapies, and one among them is selenium nanoparticles (SeNPs). Nano-selenium exhibits significant properties which make it best suited for this purpose. The article highlights the key role of SeNPs in treating major diseases like cancer, diabetes, and microbial infections.